Optimum conditions for the production of polyhydroxybutyrate from cassava wastewater by the newly isolated cupriavidus sp. KKU38 - Sangyoka, S; Poomipuk, N; Reungsang, A (Universiti Kebangsaan Malaysia, 2012)
The Cassava starch manufacturing wastewater (CSW) was used as a substrate to produce polyhydroxybutyrate (PHB) by Cupriavidus sp. KKU38. The acidogenic fermentation process of CSW was first conducted to obtain volatile fatty acids (VFAs), which are more efficient in PHB production than raw CSW. The effect on substrate concentration and nutrients, i.e. nitrogen and phosphorus concentrations, by means of chemical oxygen demand: nitrogen: phosphorus ratio (COD:N:P ratio) variation was investigated. The results indicated that PHB production from fermented CSW by Cupriavidus sp. KKU38 was optimized at the soluble COD:N:P ratio of 100:0.5:11. This ratio gave the maximum PHB content and yield of 85.53% and 0.31 g PHB/g COD consumed, respectively. By using the proposed PHB production process, the potential to produce 0.19 kg of PHB from 1.0 kg of soluble chemical oxygen demand (sCOD) contained in CSW was exhibited. The relatively high COD removal efficiency of 73.82% at the optimal condition could be achieved, which demonstrated the concept of water quality improvements alongside the production of the value-added by-product, PHB.